An Evaluation of a Novel Air Pollution Abatement System for Ammonia Emissions Reduction in a UK Livestock Building - Andrea Pacino; Antonino La Rocca; Donata Magrin; Fabio Galatioto (Atmosphere)
Agriculture and animal feeding operations are responsible for 87% of ammonia emissions in the UK. Controlling NH3 concentrations below 20 ppm is crucial to preserve workers’ and livestock’s well-being. Therefore, ammonia control systems are required for maintaining adequate air quality in livestock facilities. This study assessed the ammonia reduction efficiency of a novel air pollution abatement (APA) system used in a pig farm building. The monitoring duration was 11 weeks. The results were compared with the baseline from a previous pig cycle during the same time of year in 2023. A ventilation-controlled room was monitored during a two-phase campaign, and the actual ammonia concentrations were measured at different locations within the site and at the inlet/outlet of the APA system. A 98% ammonia reduction was achieved at the APA outlet through NH3 absorption in tap water. Ion chromatography analyses of farm water samples revealed NH3 concentrations of up to 530 ppm within 83 days of APA operation. Further scanning electron microscopy and energy-dispersive X-ray inspections revealed the presence of salts and organic/inorganic matter in the solid residues. This research can contribute to meeting current ammonia regulations (NECRs), also by reusing the process water as a potential nitrogen fertiliser in agriculture.